Assessing the Neutrality of Civil Servants When Running for Village Head - Wani Islam Suhada Yundra; Desip Triananda (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2026)
This study argues that civil servants are not neutral when they run for office and participate in village head elections. This is because neutrality has no place when civil servants are involved in the selection of village heads, even if the nomination and screening processes are separate from political party nomination mechanisms. This study aims to explain the lack of neutrality among civil servants when they run for village head. Article 43, paragraphs (1) and (2), of Government Regulation No. 43 of 2014 on the Implementing Regulations of Law No. 6 of 2014 on Villages states that civil servants may run for the office of village head with the written permission of the personnel management official. If a civil servant is elected and appointed as village head, he or she is temporarily relieved of his or her duties for the duration of the term as village head without losing his or her rights as a civil servant. On the other hand, civil servants are required by law to remain neutral in all matters. This study employs a normative legal research method using both a statutory approach and a conceptual approach.The findings of this study reveal two things: first, there is a conflict between regulations that allow civil servants to run for village head and regulations regarding civil servant neutrality; and second, it was found that, conceptually, the candidacy of civil servants for village head cannot be separated from practical political dynamics.